PERANCANGAN E-COMMERCE BERBASIS WEB PADA PT. INTI PPS PACKINDO DENGAN MENGGUNAKAN FRAMEWORK LARAVEL - Zulnalim, Kevin; Arijanto, Rudy (ALGOR, 2025)
The internet has become one of the cheapest means of communication and has a wide and unlimited reception range, therefore the internet is often used as an alternative means of running a business or business. The business sector is also affected by developments in information technology and telecommunications. Apart from being used as a means of information and communication, the internet can also be used as a process of buying and selling products, services and online news media or internet transactions between sellers and buyers, which are better known. Under the name of e-commerce. E-commerce as one of the trading activities via the internet. By utilizing e-commerce, companies can promote their products or services online, making it easier to make transactions. Many companies use e-commerce websites as a means of selling and expanding product marketing to various locations so as to increase turnover and maintain the company's existence for the long term, including PT Inti Pps Packindo, which until now still uses an offline marketing system, namely sales look for customers from one place to another to offer products. So that an electronic-based sales system is needed. The software used to design this application is PHP, MySQL, and the Laravel Framework. The method used in this test is UAT. The results of this study are the presence of an e-commerce system that can assist customers in placing orders online, find out clear and complete information on the types of products they want to buy and company profiles. This research succeeded in implementing the Laravel framework in web-based e-commerce design